ANALISIS PENCAPAIAN KEY PERFORMANCE INDICATOR (KPI) PADA SYSTEM APPLICATION AND PRODUCT (SAP) (Studi Kasus di PT. GMF AeroAsia Tbk) - Tukhas shilul Imaroh; Insan Ahmad Soleh (MIX: JURNAL ILMIAH MANAJEMEN, 2020)
PT.GMF AeroAsia in its development has an environmental impact analysis that considers the remaining spare parts so as not to overdo it. The achievement of the Key Performance Indicator (KPI) and the accuracy of the System Application and Product (SAP) are the research objectives by knowing the factors that cause the occurrence of spare parts that have been installed in the aircraft not recorded in the System Application and Product (SAP) and the efforts that can be made to achieve standard Key Performance Indicator. The method used in this research is descriptive quantitative method. The analysis tool used is Fishbone and analysis of 5W + 1H. The research data used is secondary data for 6 months (January to June 2017). The population in this research is the data of spare parts report waiting to be used (WTU) in 2016 until 2017. The sample in this research is the data of material waiting to be used report for six months from January to June. In the Pareto Diagram it was found that the most cause was due to the Robbing Material process. In the Fishbone Diagram, the main cause was found because it was not aware of the importance of updating data in the System Application and Product. The results obtained were by increasing discipline in updating the System Application and Product with the Reward and Punishment schemesaims.